2016
DOI: 10.4081/monaldi.2009.360
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of pulmonary embolism

Abstract: The diagnosis of pulmonary embolism is challenging, and autoptic series have demonstrated that a high percentage of cases are not recognized ante-mortem. A number of predisposing factors, symptoms and signs associated with pulmonary embolism have been recognized, and should be used to raise the suspicion of the disease. These include immobilization, recent surgery, active cancer, previous thromboembolism, syncope, dyspnoea, chest pain, haemoptysis, signs of deep vein thrombosis, hypocarbic hypoxemia. Once pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Duru et al (18) conducted a study on 205 patients and they found thrombi in the main PA at a rate of 14.6%. In another study, 30.8% of 31 patients had thrombi in the main PA (13). In our study, the mean NLR of the patients having the thrombus in the main PA was higher compared to the NLR found in the lobar and distal arteries groups.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Duru et al (18) conducted a study on 205 patients and they found thrombi in the main PA at a rate of 14.6%. In another study, 30.8% of 31 patients had thrombi in the main PA (13). In our study, the mean NLR of the patients having the thrombus in the main PA was higher compared to the NLR found in the lobar and distal arteries groups.…”
Section: Discussioncontrasting
confidence: 56%
“…Our study results were similar to those reported in the literature, finding out that immobilization and having undergone a recent surgery were the two most common risk factors at rates of 21.4% and 19.2%, respectively. Using the risk factors mentioned above, some scoring systems such as Wells and Geneva are used in calculating the clinical probability, but these scoring systems cannot predict the thrombus localization precisely (13). Massive PE manifests itself as persistent hypotension and/or bradycardia together with syncope or sudden cardiovascular arrest and these clinical manifestations usually occur in association with proximally located thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…This situation has brought a certain lack of confidence in the application of this rigorous approach, likely limiting its use in clinical practice. Furthermore, the continuous attempts to modify, improve and simplify these scores make it difficult to complete and compare the prospective validation studies that are much needed for a widespread diffusion of this approach [19].…”
Section: Discussionmentioning
confidence: 99%
“…PE is one of the most chronic disease, a study shows that this disease affects 500,000 to 600,000 people per year and causes 200,000 to 300,000 deaths per year in United States [2]. Another study presented in [3] shows that 100 new cases/100,000 are estimated per year in Italy [3]. According to the study presented in [4], the PE disease will become the third most chronic and mortality disease by 2030.…”
Section: Introductionmentioning
confidence: 97%